Effects of transplanting and AMF inoculation on the fruit yield of African eggplants (Solanum aethiopicum and Solanum anguivi) in Tanzania - Xu, Xiangming; Dinssa, Fekadu Fufa; Minja, Ruth; Mwaijande, Violeth; Mbwambo, Omary; Mziray, Zainab; Stavridou, Eleftheria; Bishop, Gerard J. (Frontiers in Agronomy, 2023)
African eggplant (Solanum aethiopicum L., Gilo group) is one of common traditional vegetables in Tanzania. The yield of African eggplant in Tanzania is far lower than the potential yield expected, due primarily to biotic and abiotic stresses. We conducted experiments at two locations in Tanzania to study whether plant growth and fruit yield of the Gilo group of African eggplant can be significantly improved through transplanting coupled with application of arbuscular mycorrhizal fungi (AMF) at sowing. Many plants, particularly for the directly sown treatment, died well before harvesting, and in addition many surviving plants showed wilting symptom. Transplanting of tray seedlings and using AMF at sowing led to an overall significant increase in fruit yield by 30-40% and 20-25%, respectively. Increased fruit yield per experimental plot resulted primarily from a greater number of plants that survived and reached the harvest. The exact effect of planting method (transplanting or direct sowing) and AMF amendment, however, varied greatly with plant accessions. Further research is needed to understand the cause(s) for plant mortality in order to develop appropriate plant management practices.